Kakadu, looking after the country - the Gagudju way - Breeden, Stanley, 1938- (Simon & Schuster, 1989)
Presentation in popular format of the environment of Kakadu National Park and the Gagudju peoples relation to it; Gagudju seasonality, social structure and mythology; imaginative reconstruction of the traditional life of the Badmardi clan, describes annual movement from escarpment to the floodplains, (includes Djuwarr, Gummungkuwuy, Burrungguy, Anbangbang, Nawulandja, Yuwenjgayay, Malangangerr and Ubirr), material culture, hunting (kangaroo, goose, flying fox and crocodile), gathering, camp life, food preparation, stone working and blade manufacture, fighting, rock painting, exchange and fire use; lives of contemporary Gadudju, includes Bluey Ilkirr preparing and painting bark and Felix Iyanuk, Big Bill Neidjie and Nipper Kaparegis traditional beliefs and custodial activities; contact history and the establishment of Kakadu National Park.